Recent progress of microplastic toxicity on human exposure base on in vitro and in vivo studies - Liu, Zhengguo; You, Xue-yi (The Science of the total environment, 2023)
Microplastics are widely distributed in the environment, including the atmosphere, soil and water bodies. They have been found to have toxic effects on organisms. The impact on human health is also receiving considerable attention. Microplastics can be found in drinking water, food, air and plastic products, and they can enter human body through the pathways such as ingestion, inhalation, and skin contact. After exposure to microplastics, they can induce cellular toxicity and produce toxic effects on multiple organs and systems, including the digestive, respiratory, nervous, reproductive and cardiovascular systems. This paper presents a comprehensive review and analysis on the recent progress of human exposure studies, in vitro experiments, rodent experiments, and other model experiments in microplastic human toxicity research. It comprehensively analyzes the potential human toxic effects of microplastics, providing a theoretical basis for further research on microplastic human toxicity and its mechanisms. Furthermore, this paper highlights the knowledge gaps and provides the recommendations for future research on human toxicity of microplastics. [Display omitted] •Main pathways of human exposure to microplastics are discussed.•Toxic effects of microplastics on multiple organs and systems are outlined.•Analysis of cellular toxicity of microplastics is conducted.•Organoids, computer modeling and other methods provide new research ways.•Next research directions are suggested.